Burned Out but Not Broken: Teaching Performance Amid Burnout in EFL Practicum Settings - Vanesya Eltriyana Asyifa Rinjani; Majmu'atil Husni; Muhammad Andriana Gaffar; Riki Ruswandi (Universitas Hamzanwadi, 2025)
Burnout among pre-service teachers has become an increasing concern in teacher education, especially during teaching practicum, which requires high levels of cognitive, emotional, and instructional involvement. Although there is extensive literature on burnout in in-service teachers, little research has examined its relationship with teaching performance among pre-service English as a Foreign Language (EFL) teachers in Indonesia. This study explores the link between burnout and teaching performance among 45 pre-service EFL teachers at Universitas Islam Nusantara who completed the PLP 2 (Teaching Practicum) programme. Burnout levels were assessed using the Oldenburg Burnout Inventory (OLBI), while teaching performance was measured with a researcher-developed Pre-service Teacher Performance Assessment Questionnaire (PTPAQ). Both tools were validated and found reliable, with Cronbach's alpha coefficients of 0.721 and 0.779, respectively. Because the data were not normally distributed, Spearman’s rho correlation analysis was performed. Results showed a weak and non-significant negative correlation (r = -0.219, p > 0.05) between burnout and teaching performance. These findings indicate that only. Pedagogical competence and support systems influence pre-service teaching performance more than burnout. The study emphasises the importance of teacher education programmes implementing structured mentorship and resilience-building initiatives to improve teaching quality during practicum.